Build Orientation-Driven Anisotropic Fracture Behaviour in Polymer Parts Fabricated by Powder Bed Fusion - Karthik Ram Ramakrishnan; Jagan Selvaraj (Journal of Manufacturing and Materials Processing)
Additive manufacturing (AM) enables fabricating intricate objects with complex geometries previously unattainable through conventional methods. This process encompasses various techniques, including powder bed fusion (PBF), such as selective laser sintering (SLS) and multi-jet fusion (MJF). These techniques involve selectively melting powdered polymer material, predominantly utilizing engineering thermoplastics layer by layer to create solid components. Although their mechanical properties have been extensively characterised, very few works have addressed the influence of additive manufacturing on fracture behaviour. In this context, we present our work demonstrating the presence of anisotropy in fracture behaviour due to the build orientation as well as the PBF methods. To evaluate this anisotropy, the fracture behaviour of polyamide 12 polymer manufactured by SLS and MJF were investigated with experiments and numerical modelling of Mode I compact tension (CT) specimens. Experiments were monitored by digital image correlation (DIC) and infra-red thermography (IRT). Additionally, the fractured surfaces are analysed using scanning electron microscopy. Comparative analyses between SLS and MJF technologies unveiled dissimilar trends in mechanical strength, build-orientation effects, and fracture properties.